PENERAPAN CAESAR CHIPER DAN LEAST SIGNIFICANT BIT UNTUK MENGAMANKAN DATA REKAM MEDIS - Ari Sellyana; Nur Budi Nugraha (Pusat Riset dan Inovasi Nasional, 2023)
Technological developments in data security systems in maintaining information security have grown rapidly. Medical record is a document that contains personal data and medical history and medical treatment history of a patient at a hospital. Medical records are sensitive and confidential so that not just anyone can read the information in the patient's medical record. This study aims to secure patient medical record information by encrypting it with caesar cipher cryptography, the name of the patient's disease, then from the results of the encryption, the process of inserting the encrypted information into a digital image uses the least significant bit (LSB) steganography, namely replacing 1 digit behind the binary number in every 1 bit. The results of the study show that the application created is capable of encrypting and encoding patient medical record data information and embedding this information into digital images.